The Effect of Quercetin on Coenzyme HMG-CoAR, ABCA1 Transporter, Dyslipidemia Profile and Hepatic Function in Rats Dyslipidemia Model - Ignasius Agyo Palmado; Sulistyanaengci Winarto; Honey Dzikri Marhaeny; Yusuf Alif Pratama; Chrismawan Ardianto; Junaidi Khotib (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Dyslipidemia is a lipid metabolic disorder that increases the risk of cardiovascular disease, typically marked by abnormalities in triglycerides (TG), low-density lipoprotein (LDL), and total cholesterol (TC), along with decreased high-density lipoprotein (HDL) levels. This study explored the potential of quercetin, a natural substance, as a preventive agent against dyslipidemia induced by high-fat diet (HFD) in a rat model. Simvastatin, a standard cholesterol-lowering drug, was used for the comparison. Objective: The main objective of this research was to evaluate the potential of quercetin in lipid metabolism for dyslipidemia caused by HFD and compare its effects with the first-line drug therapy simvastatin, which has a similar mechanism. Methods: Rats fed a HFD were treated with quercetin and simvastatin, and their lipid profiles, liver enzyme activities, and molecular markers related to cholesterol metabolism were analyzed. Results: Quercetin markedly decreased cholesterol levels by inhibiting the enzyme 3-Hydroxy-3-Methylglutaryl-CoA Reductase (HMG CoAR). Cellular observation revealed that it also prevented liver damage and showed a protective effect on liver enzyme activity. Quercetin enhanced the expression of the Adenosine Triphosphate Binding Cassette subfamily A member 1 (ABCA1) protein, showing a protective effect against dyslipidemia akin to simvastatin, yet with a reduced likelihood of liver toxicity. Conclusion: Quercetin may serve as an effective and safer alternative to simvastatin for treating dyslipidemia, offering cholesterol-lowering benefits without hepatotoxic risks associated with long-term statin therapy.